Decontamination of heavy metals processes, mechanisms, and applications - Chen, Jiaping Paul (Advances in industrial and hazardous wastes treatment series., 2012)
"From crystallization to membrane filtration, this book covers a wide range of subjects relating to heavy metals in the environment. The author explores the treatment, removal, recovery, disposal, management, and modeling of heavy metals. The text covers heavy adsorption processes including metal biosorption, ion exchange, and electrolysis processes for heavy metal decontamination. It also gives an overview of radioactive metals and their transportation in natural systems; presents various mathematical models for metal removal and recovery as well as transportation; and discusses a series of emerging technologies for metal treatment and management"--